2011
DOI: 10.1007/s10750-011-0913-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of configuration of instream wood on autumn and winter habitat use by fish in a large remeandering reach

Abstract: This study examined the effects of the configuration of wood structures on the use of local autumn and winter habitats by fish in a remeandering reach of a large lowland river. Fish diversity was higher at the simple wood-structure (SWS) and the log-jam (LJ) sites than at the no-wood (NW) sites during both seasons. In particular, the diversity at the LJ sites was higher than that at the SWS sites during the winter. The abundance of the four dominant fish species was generally higher at the LJ sites than at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The accumulation of detritus in low-flow areas may attract the benthic-feeding carp to the associated invertebrate community (Malmqvist et al 1978). By experimentally adding or removing structural woody habitats from stream sections, it has been shown that sections with structural woody habitats supported more and larger fish than did cleared sections (Angermeier and Karr 1984;Nagayama et al 2012). Removal of structural woody habitats from the Murray River and other rivers in south-eastern Australia has been widespread (see Koehn et al 2004), and this loss of fish habitat has often been cited as a reason for the decline of native fish populations (Cadwallader 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of detritus in low-flow areas may attract the benthic-feeding carp to the associated invertebrate community (Malmqvist et al 1978). By experimentally adding or removing structural woody habitats from stream sections, it has been shown that sections with structural woody habitats supported more and larger fish than did cleared sections (Angermeier and Karr 1984;Nagayama et al 2012). Removal of structural woody habitats from the Murray River and other rivers in south-eastern Australia has been widespread (see Koehn et al 2004), and this loss of fish habitat has often been cited as a reason for the decline of native fish populations (Cadwallader 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of structural woody habitats to riverine fish has been widely recognised with positive relationships reported for many fish species in a range of different aquatic habitats (see Crook and Robertson 1999;Dolloff and Warren 2003;Nagayama et al 2012). The reinstatement of structural woody habitats is seen as a key rehabilitation measure (MurrayDarling Basin Commission 2004;Koehn and Lintermans 2012), with the assumption that it will be used by most largebodied native fish species.…”
Section: Introductionmentioning
confidence: 99%
“…Both comparative data and experiments also provide strong evidence that fish select locations near large wood and other structures that provide refuges from high current velocities and visual isolation and overhead cover from competitors and predators (Fausch, ; Nagayama et al ., ). Slow as well as fast water velocities created by large wood provide a variety of habitat for stream fishes because habitat selection is commonly dictated by body size‐ and velocity‐dependent processes (e.g., Fausch, , ).…”
Section: Benefits and Hazards Associated With Large Woodmentioning
confidence: 99%
“…First, the geomorphic effects of wood on channel structure create pool, run, and riffle mesohabitats required by these biota to complete their life cycles, across a range of scales from reaches to riverscapes (Fausch et al, 2002). Second, the habitat complexity created by wood provides critical microhabitats that fish and other organisms need for feeding, resting, and isolation and protection from competitors and predators (e.g., Sechnick et al, 1986;Fausch, 1993;Nagayama et al, 2012). Third, stable wood pieces provide hard surfaces that support an algal food base and associated aquatic invertebrates that feed on this algae and are themselves eaten by fish (Benke and Wallace, 2003).…”
Section: Biological Benefits Of Large Woodmentioning
confidence: 99%
“…Dynamic wood jams can generate spatial and temporal morphologic heterogeneity and regulate organic matter retention (Daniels, ; Sear et al, ). By regulating organic matter and providing habitat, wood jams sustain fish and macroinvertebrates (Cashman, Pilotto, Harvey, Wharton, & Pusch, ; Jones et al, ; Nagayama, Nakamura, Kawaguchi, & Nakano, ; Pilotto, Harvey, Wharton, & Pusch, ). By interacting with bed sediment, banks, and living wood, wood jams shape channels and regulate fluvial processes (Brooks, Brierley, & Millar, ; Nakamura & Swanson, ; Scott, Montgomery, & Wohl, ).…”
Section: Introductionmentioning
confidence: 99%